Menoridade penal e medidas sócio-educativas: alguns aspectos fáticos e legais da internação em Jataí - Silveira, Divino Luiz da (2009)
This research analyzes the social-educational acts stipulated by the article 112 of the Child s and Teenager s Statute, starting from the reality of the Teenager Internment Center of Jataí (CIAJ), Goiás, especially, of the teenagers internments happened in the years of 2007 and 2008. It has the objective of verifying the effectiveness of social-educational act of internment. So, the first chapter presents a panorama of the historical understanding of children s and teenagers place in society, in matter, in the Bible, in Old Greece and Old Rome, in Middle Age and in current Brazilian context. The second chapter synthesizes the progress of the children s and teenagers guardian legislation in the world and in Brazil especially, problematizing the debate of the reduction of penal majority and the legislative reformulations of the Child s and Teenager s Statute, as well as the social-educational acts stipulated by the article 112. The third chapter approaches and evaluates the Teenager Internment Center of Jataí (CIAJ), its facilities, its characteristics, its work team and the situation and path of the teenager s interned in 2007 and in 2008. Finally, the research points that, in Jataí, the effectiveness of the social-educational act of internment and, in equal way, the social-educational act of attended freedom and the act of services rendered to community, is prejudiced exactly for the lack of implantation of precepts consigned in the Child s and Teenager Statute by the Public Power, focus on the education and socialization for teenagers which are involved in practice of crimes or of penal misdemeanors.